2012
DOI: 10.1016/j.apcatb.2012.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis/catalysis by innovative TiN and TiN-Ag surfaces inactivate bacteria under visible light

Abstract: a b s t r a c tThis study presents the design, preparation, testing and characterization of TiN and TiN-Ag nanoparticulate films leading to photocatalytic and catalytic inactivation of Escherichia coli. When Ti was sputtered in N 2 atmosphere, the TiN films unexpectedly revealed semiconductor properties when irradiated under visible light due to the formation of TiO 2 showing absorption in the visible spectral region. In TiN-Ag films, Ag enhances the photocatalytic activity of TiN leading to faster bacterial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 37 publications
(47 reference statements)
0
38
0
Order By: Relevance
“…Direct current (DC) magnetron sputtering of metals and semiconductor oxides on diverse substrates has been recently reported by our laboratory [13,14]. Fig.…”
Section: Direct Current (Dc) and Dc-pulsed (Dcp) Magnetron Sputteringmentioning
confidence: 97%
See 2 more Smart Citations
“…Direct current (DC) magnetron sputtering of metals and semiconductor oxides on diverse substrates has been recently reported by our laboratory [13,14]. Fig.…”
Section: Direct Current (Dc) and Dc-pulsed (Dcp) Magnetron Sputteringmentioning
confidence: 97%
“…2a, trace 1). This is due probably to: (a) bigger Ag-clusters hindering the diffusion of charges between TaN and the Ag layers, (b) a decrease in the number of surface catalytic sites available for bacterial inactivation [13,14], and (c) an excess of Ag acting as recombination centers for the photo-induced charges on the sample surface. Fig.…”
Section: E Coli Inactivation On Tan/ag and Taon/ag Films: Effect Of mentioning
confidence: 99%
See 1 more Smart Citation
“…The 100 lL sample of each dilution was pipetted onto a nutrient agar plate and then spread over the surface of the plate using the standard plate method. Agar plates were incubated lid down, at 37°C for 24 h prior to the counting of the bacterial colonies (Rtimi et al, 2012a(Rtimi et al, , 2012bBaghriche et al, 2012b). The bacterial data reported were replicated three times.…”
Section: Evaluation Of the Bacterial Inactivation Of Escherichia Colimentioning
confidence: 99%
“…Kelly et al (2009 and) has recently reported the antibacterial activity of sputtered nitrides films. Rtimi et al have reported TiN/ TiN-Ag and ZrN/ZrN-Ag film bacterial inactivation in the dark and under visible/actinic low intensity light irradiation (Rtimi et al, 2012a(Rtimi et al, , 2012bBaghriche et al, 2012b). The innovative objective of the present study is to report on solar induced bacterial inactivation by sputtered TiON films using laboratory scale solar simulators.…”
Section: Introductionmentioning
confidence: 99%